Delimitation of Funga as a valid term for the diversity of fungal communities: the Fauna, Flora & Funga proposal (FF&F) - Kuhar, José Francisco (2018)
As public policies and conservation requirements for biodiversity evolve there is a need for a term for the kingdom Fungi equivalent to Fauna and Flora. Thisneed is considered to be urgent in order to simplify projects oriented toward implemention of educational and conservation goals. In an informal meeting held duringthe IX Congreso Latinoamericano de Micología by the authors, the idea of clarifying this matter initiated an extensive search of pertinent terminologies. As a result ofthese discussions and reviews, we propose that the word Funga be employed as an accurate and encompassing term for these purposes. This supports the proposal of thethree Fs, Fauna, Flora and Funga, to highlight parallel terminology referring to treatments of these macrorganism of particular geographical areas. Alternative terms andproposals are acknowledged and discussed